Antihyperglycemic therapy in patients with type 2 diabetes mellitus and ischaemic heart disease: management during acute period of myocardial infarction and interventional procedures - Olga Mikhailovna Smirnova (Endocrinology Research Centre, 2012)
Current paper presents data from international multicenter studies performed with participation of patients with type 2 diabetes mellitus(T2DM) and ischaemic heart disease. We analyze results regarding advisability of different glycemic targets, prescription safetyof various classes of antihyperglycemic agents in patients with inschaemic heart disease, acute coronary syndrome and chronic heartfailure, as well as therapeutic approach to glycemic control in acute myocardial infarction and cardiologic interventional procedures.